1999
DOI: 10.1002/nvsm.57
|View full text |Cite
|
Sign up to set email alerts
|

Cause‐related marketing and values in Australia

Abstract: An investigation is conducted into attitudes towards cause-related marketing (CRM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 27 publications
6
60
0
Order By: Relevance
“…Forms of business support include cash donations, which continue to be a highly significant form of nonprofit income (Sargeant and Jay, 2004), donations of stocks and shares, enhancing the nonprofit's public profile (Himmelstein, 1997;Wagner and Thompson, 1994), gifts of in-kind products/services (Elischer, 2002), staff time (Sagawa and Segal, 2000;Smith, 1994), sponsorship (Mescon and Tilson, 1987), fundraising from staff/payroll giving and fundraising from customers. In respect of the latter, the topic of cause related marketing has received a great deal attention with a particular emphasis on profiling the individuals most likely to respond to such an appeal (e.g Ross et al, 1991;Kropp et al, 1999 and the well publicized Cone/Roper studies in the United States).…”
Section: Extant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Forms of business support include cash donations, which continue to be a highly significant form of nonprofit income (Sargeant and Jay, 2004), donations of stocks and shares, enhancing the nonprofit's public profile (Himmelstein, 1997;Wagner and Thompson, 1994), gifts of in-kind products/services (Elischer, 2002), staff time (Sagawa and Segal, 2000;Smith, 1994), sponsorship (Mescon and Tilson, 1987), fundraising from staff/payroll giving and fundraising from customers. In respect of the latter, the topic of cause related marketing has received a great deal attention with a particular emphasis on profiling the individuals most likely to respond to such an appeal (e.g Ross et al, 1991;Kropp et al, 1999 and the well publicized Cone/Roper studies in the United States).…”
Section: Extant Researchmentioning
confidence: 99%
“…Much has been written about this continuum which runs from purely altruistic corporate philanthropy (Cowton, 1987;Shaw and Post, 1993;Campbell et al, 1999) through to strategic, commercially based initiatives that are focused on direct return on investment to the company such as cause related marketing and sponsorships (Varadarajan and Menon, 1988;Kropp et al, 1999). For the purpose of this study corporate community involvement (CCI) describes the portfolio of activities through which a company engages with its community.…”
Section: Introductionmentioning
confidence: 99%
“…The literature of cause-related marketing [14,15] also showed that the advertisement of cause-related marketing has a positive effect on purchase intentions. People purchase the product of cause-related marketing not just for their own profit, but the happiness appeared via helping others.…”
Section: Introductionmentioning
confidence: 98%
“…This instrument was developed by analogy to the tool employed by Kropp et al [1999]. More precisely, four seven-point Likert-type scales were used.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies addressing links between values and CRM responses were done on convenient samples, consistent of students [Kropp et al 1999;Lavack 2003;Westberg, Pope 2005]. Using students as subjects makes findings hardly generalizable and could bias results [Peterson 2001].…”
Section: Introductionmentioning
confidence: 99%